Inhibition of Aβ42 oligomerization in yeast by a PICALM ortholog and certain FDA approved drugs - Sei-Kyoung Park; Kiira Ratia; Mariam Ba; Maria Valencik; Susan W. Liebman (Microbial Cell, 2016)
The formation of small Aβ42 oligomers has been implicated as a toxic species in Alzheimer disease (AD). In strong support of this hypothesis we found that overexpression of Yap1802, the yeast ortholog of the human AD risk factor, phosphatidylinositol binding clathrin assembly protein (PICALM), reduced oligomerization of Aβ42 fused to a reporter in yeast. Thus we used the Aβ42-reporter system to identify drugs that could be developed into therapies that prevent or arrest AD. From a screen of 1,200 FDA approved drugs and drug-like small compounds we identified 7 drugs that reduce Aβ42 oligomerization in yeast: 3 antipsychotics (bromperidol, haloperidol and azaperone), 2 anesthetics (pramoxine HCl and dyclonine HCl), tamoxifen citrate, and minocycline HCl. Also, all 7 drugs caused Aβ42 to be less toxic to PC12 cells and to relieve toxicity of another yeast AD model in which Aβ42 aggregates targeted to the secretory pathway are toxic. Our results identify drugs that inhibit Aβ42 oligomers from forming in yeast. It remains to be determined if these drugs inhibit Aβ42 oligomerization in mammals and could be developed as a therapeutic treatment for AD.